Dibenzo heterocyclic-terminated spiro-type hole transporting materials for perovskite solar cells. Issue 30 (21st July 2022) - Liang, Yongpeng; Chen, Jianlin; Zhang, Xianfu; Han, Mingyuan; Ghadari, Rahim; Wu, Nan; Wang, Ying; Zhou, Ying; Liu, Xuepeng; Dai, Songyuan
Abstract : spiro-DBF exhibits higher hole mobility, better morphology and stronger hole extraction ability than spiro-OMeTAD, resulting in a higher PCE. Abstract : Spiro-type molecules remain benchmark hole transporting materials (HTMs) for high-performance perovskite solar cells (PSCs). Terminal unit engineering of spiro-type HTMs has drawn much attention to efficient and stable PSCs. In this work, we introduce dibenzofuran or dibenzothiophene as the terminal group into the spiro-type HTMs, named spiro-DBF and spiro-DBT, respectively, due to their superior carrier transport properties. The structure–property relationship introduced by varied terminal groups is studied in detail. It is noted that the molecule (spiro-DBF) with dibenzofuran edge groups exhibits higher hole mobility, better morphology on the perovskite layer and stronger hole extraction ability than spiro-OMeTAD. When used in PSCs, spiro-DBF exhibits a PCE of 21.43%, which is even higher than that of conventional spiro-OMeTAD. Moreover, the device with spiro-DBF also exhibits superior long-term stability. Thus, the results deliver some new insights for developing perfect HTMs and spiro-DBF could also be a potential HTM candidate for high-performance PSCs.